KOMUNIKASI PARIWISATA 4.0: ANALISIS KAMPANYE DIGITAL DESTINASI WISATA MANDALIKA DAN RAJA AMPAT MELALUI VLOG JOKOWI - Prayitno, Yudanto; Fitriani, Dinda Rakhma; Eviyani, Eviyani (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2020)
Video Blog (Vlog) President Joko Widodo on social media Youtube is a Vlog that is quite well known in cyberspace. In President Joko Widodo's Vlog, there are several videos related to Indonesian tourism including #JKWVLOG Indah Mandalika and #JKWVLOG Raja Ampat. President Joko Widodo conducts Vlogging activities in the two tourist destinations. This study aims to analyze the campaign destinations of Mandalika and Raja Ampat tourist destinations. This research method uses qualitative methods with case studies to analyze the digital campaigns of Mandalika and Raja Ampat tourist destinations. Data collection techniques used were documentation studies, observational studies, interviews, literature studies, data searches carried out online. Tourism communication 4.0 is digital communication which is influenced by information and communication technology. This technological change is accompanied by a change in the culture of people who like to share photos and videos. These cultural changes should be used to campaign for Mandalika and Raja Ampat tourist destinations. Mr. Jokowi has given an example in the Mandalika and Raja Ampat tourist destination campaigns by utilizing social media which is more trend, especially vlogs. The use of vlogs by Mr. Jokowi is one form of tourism communication 4.0.